(untitled) (Coordinates of Public Administration, 2026)
The article examines the current problems and prospects of developing Ukraine’s legal policy in the context of socio-political transformation and martial law. Legal policy is considered as a key instrument for ensuring the rule of law, constitutional order, and stability of public governance under crisis conditions. The paper analyzes the challenges faced by the state since the beginning of Russian aggression in 2014 and its full-scale escalation in 2022, including institutional disintegration, fragmentation of law-making, limited access to justice, and problems of implementing human rights and freedoms. The article outlines the priority directions of legal policy modernization, including the digitalization of law-making and law-enforcement procedures, strengthening anti-corruption infrastructure, reforming the judiciary, and developing decentralization. Special attention is paid to aligning Ukraine’s legal policy with European standards, in particular the case law of the European Court of Human Rights, the recommendations of the Venice Commission, and the requirements of the acquis communautaire. The importance of implementing the principles of good governance as the basis for democratic transformation is emphasized. It is concluded that the development of Ukraine’s legal policy should be carried out as a comprehensive process aimed at combining security and democratic priorities, ensuring institutional resilience, strengthening the rule of law, and integrating into the legal space of the European Union.